2023
DOI: 10.1002/ptr.8020
|View full text |Cite
|
Sign up to set email alerts
|

Natural compounds against nonalcoholic fatty liver disease: A review on the involvement of the LKB1/AMPK signaling pathway

Navid Omidkhoda,
Sina Mahdiani,
A. Wallace Hayes
et al.

Abstract: Although various therapeutic approaches are used to manage nonalcoholic fatty liver disease (NAFLD), the best approach to NAFLD management is unclear. NAFLD is a liver disorder associated with obesity, metabolic syndrome, and diabetes mellitus. NAFLD progression can lead to cirrhosis and end‐stage liver disease. Hepatic kinase B1 (LKB1) is an upstream kinase of 5′‐adenosine monophosphate‐activated protein kinase (AMPK), a crucial regulator in hepatic lipid metabolism. Activation of LKB1/AMPK inhibits fatty aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 159 publications
0
1
0
Order By: Relevance
“…Alkaloids are a class of nitrogen-containing organic secondary metabolites with diverse structures and have a wide range of biological functions, including anti-inflammatory, antioxidant, antitumor and immunomodulatory effects ( Liu et al, 2023 ; Omidkhoda et al, 2023 ). Several studies have shown that the effects of alkaloids on NAFLD/ALD are mediated through the regulation of gut flora.…”
Section: Role Of Natural Products and Their Extracts In Fatty Liver D...mentioning
confidence: 99%
“…Alkaloids are a class of nitrogen-containing organic secondary metabolites with diverse structures and have a wide range of biological functions, including anti-inflammatory, antioxidant, antitumor and immunomodulatory effects ( Liu et al, 2023 ; Omidkhoda et al, 2023 ). Several studies have shown that the effects of alkaloids on NAFLD/ALD are mediated through the regulation of gut flora.…”
Section: Role Of Natural Products and Their Extracts In Fatty Liver D...mentioning
confidence: 99%